Controlling CO2 hydrogenation selectivity by Rh-based catalysts with different crystalline phases of TiO2. Issue 26 (11th March 2022) - Cao, Fenghai; Gong, Nana; Ma, Zixuan; Wang, Xiaoxing; Tan, Minghui; Wu, Yingquan; Tan, Yisheng
Abstract : The metal–support interactions could achieve the regulation of CO2 hydrogenation selectivity by modulating the support crystal phases. Abstract : A series of Rh-based catalysts with various crystalline phases (p25, anatase, and rutile) were prepared via the incipient-wetness impregnation method. It was found that these catalysts had different metal–support interactions. Hence, 1%Rh/p, 1%Rh/r, and 1%Rh/a exhibited methane, CO, and methanol selectivity, respectively.